2016
DOI: 10.1073/pnas.1523693113
|View full text |Cite
|
Sign up to set email alerts
|

Pten loss promotes MAPK pathway dependency in HER2/neu breast carcinomas

Abstract: Loss of the tumor suppressor gene PTEN is implicated in breast cancer progression and resistance to targeted therapies, and is thought to promote tumorigenesis by activating PI3K signaling. In a transgenic model of breast cancer, Pten suppression using a tetracyclineregulatable short hairpin (sh)RNA cooperates with human epidermal growth factor receptor 2 (HER2/neu), leading to aggressive and metastatic disease with elevated signaling through PI3K and, surprisingly, the mitogen-activated protein kinase (MAPK) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 44 publications
3
49
0
Order By: Relevance
“…Intrinsic or de novo acquired resistance to HER2‐therapies has been described (Rexer and Arteaga, 2012) and no screening test to predict resistance to these therapies is currently available. In previous experimental studies, as well as in breast cancer patients, the contribution of an inactivation of the PTEN gene to the development of resistance against HER2‐targeting therapies in patients with HER2‐positive tumors has been reported (Burnett et al., 2015; Ebbesen et al., 2016). Moreover, it has been suggested that mutations in the PIK3CA gene play an important role in mechanisms leading to this resistance (Ahmad et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic or de novo acquired resistance to HER2‐therapies has been described (Rexer and Arteaga, 2012) and no screening test to predict resistance to these therapies is currently available. In previous experimental studies, as well as in breast cancer patients, the contribution of an inactivation of the PTEN gene to the development of resistance against HER2‐targeting therapies in patients with HER2‐positive tumors has been reported (Burnett et al., 2015; Ebbesen et al., 2016). Moreover, it has been suggested that mutations in the PIK3CA gene play an important role in mechanisms leading to this resistance (Ahmad et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…S3B; Muller et al 1988). Female MMTV-Neu mice develop multifocal palpable mammary tumors efficiently after pregnancy (Ebbesen et al 2016). We generated FVB-Tg(MMTV-ErbB2) NK1Mul/J/miR-424(322)/503 −/− animals (MMTV-NeumiR_KO) and compared the expression of IGF1R, BCL-2, and CDC25A in size-matched tumors (0.5-0.8 cc) with MMTV-Neu animals.…”
Section: Cdc25a Bcl-2 and Igf1r Oncogenes Are Up-regulated In Mir-4mentioning
confidence: 99%
“…Oncogenic MAPK signaling results in the production of immunosuppressive factors (e.g., VEGF, IL-6 and IL-10), which inhibit the proliferation and activation status of tumor-specific T cells and DCs [91]. In line with this, loss of the tumor suppressor gene PTEN has been shown to correlate with resistance against cancer immunotherapies, through the enhanced signaling of both the MAPK and PI3K signaling cascades [92,93]. Activation of the PI3K-AKT-mTOR pathway can contribute to therapy resistance by directly promoting tumor cell proliferation and survival, as well as the upregulation of PD-L1 cell surface expression, thereby inhibiting the function of local effector T cells [94].…”
Section: Tumor Cell Intrinsic Primary Resistance Mechanismsmentioning
confidence: 93%